PENINGKATAN AKSEBILITAS INFORMASI MELALUI PEMBUATAN PAPAN TANDA PENGENAL RUMAH APARAT DESA SIMUNTU - Widiyatmi Widiyatmi; Nursafitri Nursafitri; Sumiati Sumiati; Adelia Adelia; Anisa K. Saum; Nasrudin Nasrudin; Muh Fiqi; Melda Melda; Moh. Nasril (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
Information transparency at the village level is crucial in providing transparent, fast, and efficient public services. One of the challenges faced by the people of Simuntu Village is the difficulty in locating the homes of village officials when requiring services outside of office hours. Newcomers to the village experience similar challenges, often resulting in delays in coordination and service processes. This community service initiative aims to describe and implement the creation of identification signs for village officials' homes that only display the official's position, without personal names, as an innovation to improve public information accessibility. The method used was a participatory approach involving the village government and the community, through observation, interviews, and the design, construction, and installation of the signs, along with documentation of the activities. The results of implementing the initiative indicate that the presence of identification signs facilitates community members and newcomers in locating village officials based on their service needs, accelerates coordination, and improves the effectiveness of public services at the village level. Furthermore, the use of position-based signs is considered to strengthen transparency in public information without compromising the privacy and security of village officials. Thus, this initiative contributes positively to supporting more informative, responsive, and public service-oriented village governance.